RANCANG BANGUN WELDING FIXTURE PADA PROSES PENGELASAN PRODUK INNER JOINT UNTUK MENGURANGI PRODUK NG (NOT GOOD) DAN MENURUNKAN WAKTU PROSES PRODUKSI DI PT YOGYA PRESISI TEHNIKATAMA INDUSTRI - Manggala, Taruna; Nugroho, Wahyu Isti; Khoryanton, Ampala (Politeknik Negeri Semarang, 2024)
The background and problems in this research are the welding process of inner joint products at PT Yogya Presisi Tehnikatama Industri where there are not good (NG) products and the welding process time can be shortned if there is a support tool for operator. The purpose of this study is to prevent NG products from inner joints and reduce the production process time of inner joints. The method used in this study is to use a flow diagram for design. The first stage is to identify the problem with the 5M + 1E collected factor followed by conducting field studies, staff interviews, and literature studies. The second stage is to design the welding fixture inner joint using Solidworks 2019 software with dimensions of 165 mm in length, 301 mm in width, and 262.42 mm in height composed of 19 single components made of ASTM A36 steel and a standart part. The third stage is the process of making welding fixtures which includes material procurement to the CNC milling, CNC lathe, and plate bending processes followed by fixture assembly. The test results showed a decrease in NG products by 22.58% and a decrease in welding process time by 30.93%.